2020
DOI: 10.3847/1538-4357/ab660a
|View full text |Cite
|
Sign up to set email alerts
|

Hot Subdwarf Stars Identified in Gaia DR2 with Spectra of LAMOST DR6 and DR7. I. Single-lined Spectra

Abstract: 182 single-lined hot subdwarf stars are identified by using spectra from the sixth and seventh data release (DR6 and DR7) of the Large Sky Area Multi-Object Fibre Spectroscopic Telescope (LAMOST) survey. We classified all the hot subdwarf stars using a canonical classification scheme, and got 89 sdB, 37 sdOB, 26 sdO, 24 He-sdOB, 3 He-sdO and 3 He-sdB stars, respectively. Among these stars, 108 hot subdwarfs are newly discovered, while 74 stars were reported by previous catalogs. The atmospheric parameters of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(74 citation statements)
references
References 94 publications
4
70
0
Order By: Relevance
“…10, we show the distributions of the radial velocities of the hot subdwarfs for different α CE , where their orbital inclinations i are uniformly generated in cos i. Here, we only show the cases with τ sp = 10 7 yr, because a spindown time scale of a few 10 6 yr may be necessary for SNe Ia (Soker 2018; Meng & Podsiadlowski (Németh et al 2012) and LAMOST (Luo et al 2016(Luo et al , 2019Lei et al 2019Lei et al , 2020 surveys, where the stars with significant binary signals are excluded. Two sequences for He weak subdwarfs and more He-rich ones are shown by dashed and dot-dashed lines, respectively.…”
Section: The Mass and Orbital Velocity Of The Companions At Supernova...mentioning
confidence: 99%
See 1 more Smart Citation
“…10, we show the distributions of the radial velocities of the hot subdwarfs for different α CE , where their orbital inclinations i are uniformly generated in cos i. Here, we only show the cases with τ sp = 10 7 yr, because a spindown time scale of a few 10 6 yr may be necessary for SNe Ia (Soker 2018; Meng & Podsiadlowski (Németh et al 2012) and LAMOST (Luo et al 2016(Luo et al , 2019Lei et al 2019Lei et al , 2020 surveys, where the stars with significant binary signals are excluded. Two sequences for He weak subdwarfs and more He-rich ones are shown by dashed and dot-dashed lines, respectively.…”
Section: The Mass and Orbital Velocity Of The Companions At Supernova...mentioning
confidence: 99%
“…Here, we collected the atmospheric parameters of some hot subdwarfs from the GALEX and LAMOST surveys (Németh et al 2012, Luo et al 2016Lei et al 2019Lei et al , 2020, and plotted them into a log(N He /N H ) × log g − log T eff plane (Fig. 11), where the stars with significant binary signals are excluded.…”
Section: Comparison With Observationsmentioning
confidence: 99%
“…K-means method is one of the most widely used clustering methods. It is often used in astronomy to study stellar and galaxy spectra, X-ray spectra, asteroids spectra, and so on [18], [43], [44]. However, K-means is not optimized to detect outliers, which needs to randomly select k objects as the initial centroids and repeat iteratively until reaching convergence.…”
Section: B Unsupervised Learningmentioning
confidence: 99%
“…M. Perpinya-Valles et al reported the discovery of J1953-1019, the first resolved triple white dwarf system based on Gaia DR2 photometry and astrometry combined with the follow-up spectroscopy [11], and many other authors also detect the WDMS from various astronomical data [12]- [16]. In addition, Lei et al identified 294 hot subdwarf stars from LAMOST DR5 [17] and 182 single-lined hot subdwarf stars by using atmospheric parameter and spectral lines from LAMOST DR6 and DR7 [18]. Wang et al proposed a method based Lick-index for excavation and analysis of outliers from massive stellar spectra [19].…”
Section: Introductionmentioning
confidence: 99%
“…SDSS (the Sloan Digital Sky Survey [1,2]) and LAMOST (the Large Sky Area Multi-Object Fiber Spectroscopic Telescope [3,4]) are the two most ambitious spectroscopic surveys worldwide. The latest and final data release of optical spectra of SDSS is data release 16. LAMOST has been upgraded to have both low-and medium-resolution modes of observation and has finished data release 7 (DR7) [5] which is the product of the medium-resolution spectra (MRS) survey…”
Section: Introductionmentioning
confidence: 99%